2018
DOI: 10.1186/s12889-018-5834-6
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and the onset of depressive symptoms among middle-aged and older adults in China: evidence from the CHARLS

Abstract: BackgroundThe association between obesity and depression has been documented in previous systematic studies but remains controversial. Many prospective studies have focused on children and youth, and several studies have examined this relationship among older populations. This study of the changes in obesity status aimed to examine the association between depression and obesity among middle-aged and elderly adults in China.MethodsThe data originated from the follow-up survey (2011 and 2013–2015) of the China H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
83
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(104 citation statements)
references
References 38 publications
8
83
3
Order By: Relevance
“…In the logistic regression we found that BMI and female gender were independent risk factors for depressive symptoms, which were in line with previous studies [20][21][22][23] . Luo et al [20] reported that the relationship between weight and depressive symptoms is negatively associated among females and males within the normal BMI range. Zhou et al [23] found that there was a negative association between BMI and depressive symptoms for males.…”
Section: Discussionsupporting
confidence: 92%
“…In the logistic regression we found that BMI and female gender were independent risk factors for depressive symptoms, which were in line with previous studies [20][21][22][23] . Luo et al [20] reported that the relationship between weight and depressive symptoms is negatively associated among females and males within the normal BMI range. Zhou et al [23] found that there was a negative association between BMI and depressive symptoms for males.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, a nonsignificant negative association between depression and obesity has also been reported previously ( 12 , 43 ). In contrast, several studies reported a significant positive association between depression and obesity ( 11 , 12 , 20 , 21 , 44 , 45 ). Young people regarded thinness as a beauty symbol.…”
Section: Discussionmentioning
confidence: 81%
“…And regarding the significant morbidity of depression with obesity, various studies found a close association between obesity and depression [32][33][34][35][36][37] due to the positive relation between depression and emotional eating [38] as well as the associated poor body image, lack of competence, interpersonal problems, and internalization of weight bias with obesity [32].…”
Section: Discussionmentioning
confidence: 99%